2018
DOI: 10.1080/02602938.2018.1545896
|View full text |Cite
|
Sign up to set email alerts
|

The impact of formative peer feedback on higher education students’ academic writing: a Meta-Analysis

Abstract: Peer feedback is frequently implemented with academic writing tasks in higher education. However, a quantitative synthesis is still lacking for the impact that peer feedback has on students' writing performance. The current study conveyed two types of observations. First, regarding the impact of peer feedback on writing performance, this study synthesized the results of 24 quantitative studies reporting on higher education students' academic writing performance after peer feedback. Engagement in peer feedback … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
100
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(114 citation statements)
references
References 62 publications
5
100
0
9
Order By: Relevance
“…For this reason, peer-assisted learning strategies could interfere as effective ways to help students receive feedback, instructions, and reinforcement from their classmates more frequently than a teacher could provide (S. E. Carr et al, 2016). Peer feedback is provided by equal status learners and can be regarded as a form of formative assessment -the counterpart of teacher feedback (Huisman, Saab, van den Broek, & van Driel, 2019), and also as a form of collaborative learning (Van Gennip, Segers, & Tillema, 2010). In both cases, the learner expects an intermediate check of his performance against the criteria, accompanied by feedback on his strengths, weaknesses and/or tips for improvement (Aljadeff-Abergel, Peterson, Wiskirchen, Hagen, & Cole, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, peer-assisted learning strategies could interfere as effective ways to help students receive feedback, instructions, and reinforcement from their classmates more frequently than a teacher could provide (S. E. Carr et al, 2016). Peer feedback is provided by equal status learners and can be regarded as a form of formative assessment -the counterpart of teacher feedback (Huisman, Saab, van den Broek, & van Driel, 2019), and also as a form of collaborative learning (Van Gennip, Segers, & Tillema, 2010). In both cases, the learner expects an intermediate check of his performance against the criteria, accompanied by feedback on his strengths, weaknesses and/or tips for improvement (Aljadeff-Abergel, Peterson, Wiskirchen, Hagen, & Cole, 2017).…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 One method to achieve this is through student peer review, which places the student as an active participant in feedback to foster self-reflection and higher order thought processes such as knowledge application and problem solving 17 , 18 Student peer review has been shown to be an effective feedback approach such as to improve academic writing. 19 …”
Section: Introductionmentioning
confidence: 99%
“…It is for this and many other reasons, peer review has been researched by many academics working in various subjects, especially in the field of English language training. Researchers addressed, for example, an array of issues linked to positive impact of peer review on enhancing students' writing skills (Bainbridge & Sandford-Couch, 2018;Huisman et al, 2019;Liu & Carless, 2006;Malyuga, 2009;Min, 2006;Mulder et al, 2014;Nicol, 2014). However, "student perceptions of formative peer review remain relatively understudied" (Mulder et al, 2014, 159), especially in the field of formative inclass oral peer review of presentations made by students or any other oral activities, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of formative peer review is based on the definition of peer assessment by Topping (1998) and the definition of formative peer feedback for writing performance provided by Huisman et al (2019). In-class formative peer review is defined in our research as an arrangement whereby students communicate information to peers of similar status, which may contribute to the improvement of presentation, language or any other relevant skills of the student delivering a presentation.…”
Section: Introductionmentioning
confidence: 99%